Beauty As World Transposition: Fairy Tale Adaptation in Imperfect (2019) from Memoir to Film - Pujiati, Hat; Rengganis, Ririe (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Fairy tales shape most girls’ formative years, introducing them to fairies who guide them toward meeting Prince Charming on a white horse, marrying, and living happily ever after. Imperfect, a memoir of self-acceptance written by Meira Anastasia and adapted into a film of the same title, represents a related construction of beauty that parallels Charles Perrault’s fairy tale Beauty and the Beast. The concept of beauty serves as the central element in the fairy tale, revealing similar patterns in both the memoir and its film adaptation. Beauty constructions established in Beauty and the Beast over the past four centuries remain significant for contemporary women. This article examines two key questions: How does beauty adaptation function as world transposition from the fairy tale to reconstruct women’s worlds in Imperfect? What ideological and cultural implications emerge from this adaptation? We apply Linda Hutcheon’s theory of adaptation to address these questions through a multi-perspectival approach. Our findings reveal that the interpellation of beauty construction appears within the intimate emotional narrative mode embedded in the story’s genre. The beauty transposition from the fairy tale reconstructs women’s worlds, moving from Renaissance humanism to postmodernist subjectivism. This study contributes uniquely to adaptation studies by analyzing memoir as source text rather than traditional literary works, demonstrating how Indonesian cultural contexts indigenize European fairy tale beauty standards, and revealing how different media forms create distinct mechanisms of resistance to patriarchal beauty discourse.